2016
DOI: 10.1530/erc-16-0037
|View full text |Cite
|
Sign up to set email alerts
|

Brachyury, a vaccine target, is overexpressed in triple-negative breast cancer

Abstract: Patients diagnosed with triple negative breast cancer (TNBC) have a high rate of tumor metastasis and a poor prognosis. The treatment option for these patients is currently chemotherapy, which results in very low response rates. Strategies that exploit the immune system for the treatment of cancer have now shown the ability to improve survival in several tumor types. Identifying potential targets for immune therapeutic interventions is an important step in developing novel treatments for TNBC. In this study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 49 publications
0
33
1
Order By: Relevance
“…Tumor cells undergoing this phenotypic transition exhibit enhanced motility and invasiveness in vitro , a propensity to metastasize in vivo , and features of tumor stemness (16), including resistance to a range of therapeutics such as chemotherapy, radiation, small molecule therapies, and, potentially, immunotherapy (1720). In agreement with a role for brachyury in the progression of carcinomas, multiple studies have now shown that the level of brachyury in the primary tumor correlates with poor patient prognosis in carcinomas of the lung (21), colon (6), breast (9), triple-negative breast (10), and gastrointestinal stromal tumor (GIST) (22). Brachyury expression has also been shown to be correlated with advanced-stage prostate cancer (8).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Tumor cells undergoing this phenotypic transition exhibit enhanced motility and invasiveness in vitro , a propensity to metastasize in vivo , and features of tumor stemness (16), including resistance to a range of therapeutics such as chemotherapy, radiation, small molecule therapies, and, potentially, immunotherapy (1720). In agreement with a role for brachyury in the progression of carcinomas, multiple studies have now shown that the level of brachyury in the primary tumor correlates with poor patient prognosis in carcinomas of the lung (21), colon (6), breast (9), triple-negative breast (10), and gastrointestinal stromal tumor (GIST) (22). Brachyury expression has also been shown to be correlated with advanced-stage prostate cancer (8).…”
Section: Introductionmentioning
confidence: 61%
“…Subsequent studies have found that brachyury is absent in most normal adult human tissues, with the exception of low levels found in normal testis, thyroid, and a subset of B cells (2,3). High levels of brachyury have been found, however, in the primary and/or metastatic sites of non-small cell lung cancer (NSCLC) and small cell lung cancer (4,5), colon (6), hepatocellular (7), prostate (8), and breast carcinomas (9), including triple-negative breast cancer (TNBC) (10). High levels of brachyury are also characteristic of chordoma (11,12), a rare tumor type thought to originate from remnants of the notochord where brachyury is normally found in the human embryo.…”
Section: Introductionmentioning
confidence: 99%
“…However, this expression was also statistically significantly related to ER+ status, in contrast to the findings of previous studies (p = 0.005). 25,38 An association between the subtypes of breast cancer and brachyury seems to be present, but there have been few studies on this topic, and further research is needed in the future. The brachyury index was highest in the NR group (mean = 171.7; SD = 67.9) and lowest in the pCR group (mean = 130.0; SD = 84.3), but this difference was not statistically significant (p = 0.625), although the finding might be related to the poor treatment outcome, similar to previous study results.…”
Section: Discussionmentioning
confidence: 99%
“…The brachyury index was calculated by multiplying the percentage of positive cells by the staining intensity. 25 …”
Section: Ihc Scoringmentioning
confidence: 99%
“…Clinical evidence suggesting an association between tumor phenotypic transitions and cancer progression includes the results of multiple correlative studies demonstrating a positive association between the expression of mesenchymal markers (such as vimentin or N-cadherin) and/or the loss of epithelial E-cadherin in clinical samples with poor prognosis (Gravdal et al, 2007; Tan et al, 2014). Similarly, aberrant expression of transcriptional drivers of the mesenchymal phenotype, including SNAI1, SNAI2, brachyury, and others have been positively correlated with poor clinical outcome in a range of human tumor types (Blanco et al, 2002; Elloul et al, 2005; Gravdal et al , 2007; Hamilton et al, 2016b; Palena et al, 2014; Pinto et al, 2014). Direct evidence for a role of this phenomenon in tumor metastasis, however, originates from murine models of cancer.…”
Section: Tumor Mesenchymalization Underlies Metastasis Stemness Andmentioning
confidence: 99%